Prediction of the compressibility behavior of highly plastic clays under high stresses - GÜRTUĞ, YEŞİM (ELSEVIER SCIENCE BV, 2011)
A simple method is proposed to predict the compressibility behavior of highly plastic clays (bentonites/montmorillonites) under high pressures using data describing their behavior under low pressures. It was shown that the void ratio of the compressible layer at 100 kPa is an effective normalizing factor to predict the void ratio at higher pressures. Experimental results from the published literature on highly plastic clays were used to verify the proposed procedure. The different normalized equations, that are, i) e/e(100) vs. log pressure p and ii) e/e(100) with 1/root p, were studied. Both of the equations yielded very good results in predicting the compressibility behavior under high pressures. Extremely high correlation was found out to exist between the proposed equation and the equation obtained using the diffuse double layer theory. Given the need to obtain the compressibility behavior and the difficulties involved in the experimental work to obtain reliable results at high pressures, the proposed method was found out to be very effective. (c) 2010 Elsevier B.V. All rights reserved.
Keywords: Clays; Compressibility; Consolidation; Laboratory test; Mineralogy; High stresses